SHORT TERM DEFLECTION OF ORDINARY, PARTIALLY PRESTRESSED AND GFRP BARS REINFORCED CONCRETE BEAMS (Journal of Engineering, 2010)
The behavior of structural concrete beams is studied under short-term loading. A computer program developed originally by Oukaili to evaluate curvature is modified to evaluate the deflection for flexural structural concrete members. The program deals with actual stress-strain relationships of concrete and steel. The analysis is based on requirements of equilibrium and compatibility of strain in concrete and reinforcement. The proposed model is used in conjunction with the step by step analysis for small loading increments that allows the determination of the history of strain and stress in concrete with prestressing steel or non-prestressing reinforcement only or prestressing and non-prestressing reinforcement together. The evaluation of curvatures for the structural member involves iterations for computing the strains vectors at each analysis step. Newmark's numerical integration is used to evaluate the deflection of the member depending on the curvature values. The stress-strain model that was proposed by (Korpenko et al. 1986) is used and compared with experimental data and other analytical models for each of concrete and steel. The comparison showed good agreement between the model used and the experimental data. This relationship is used in SECTION program and presented in this study. The analytical results for load-deflection diagram are compared with available experimental data. The comparison has shown good agreement.